Novel Mechanistic Insights into Ectodomain Shedding of EGFR Ligands Amphiregulin and TGF-α: Impact on Gastrointestinal Cancers Driven by Secondary Bile Acids - Nagathihalli, Nagaraj S. (2014)
Secondary bile acids (BAs) such as deoxycholic acid (DCA) promote the development of several gastrointestinal malignancies, but how they mediate this effect is unclear. In this study, we offer evidence of a mechanism involving ectodomain shedding of the EGFR ligands amphiregulin (AREG) and TGF-α which rely upon the cell surface protease TACE/ADAM-17. Specifically, we show that AREG participates in DCA-induced EGFR and STAT3 signaling, cell cycle progression and tumorigenicity in human colorectal cancer (CRC) and pancreatic ductal adenocarcinoma (PDAC). TACE and AREG, but not TGF-α, were overexpressed in both CRC and PDAC tissues compared to normal tissues. Exposure of CRC and PDAC cells to DCA resulted in co-localization of Src and TACE to the cell membrane, resulting in AREG-dependent activation of EGFR, MAPK and STAT3 signaling. Src or TACE inhibition was sufficient to attenuate DCA-induced AREG, but not TGF-α shedding. We also examined a role for the bile acid transporter TGR5 in DCA-mediated EGFR and STAT3 signaling. RNAi-mediated silencing of TGR5 or AREG inhibited DCA-induced EGFR, MAPK and STAT3 signaling, blunted cyclin D1 expression and cell cycle progression, and attenuated DCA-induced CRC or PDAC tumorigenicity. Together, our findings define an AREG-dependent signaling pathway that mediates the oncogenic effects of secondary BAs in gastrointestinal cancers, the targeting of which may enhance therapeutic responses in their treatment.